HYDRAULIC AND STATISTICAL GRAIN-SIZE PARAMETERS OF PINDOS TURBIDITE DEPOSITS - Ananiadis, G.; Vakalas, I.; Kontopoulos, N.; Zelilidis, A. (Bulletin of the Geological Society of Greece, 2018)
Final closure of the Pindos ocean, resulted in collision of Apulia with Pelagonian microplates, produced voluminous clastic sediments that flowed southwards as turbidity currents in the form of submarine fans, giving rise to Pindos flysch during early Tertiary. Samples coming from thinbedded sandstones were collected from five cross-sections throughout Pindos flysch in order to determine the characteristics of the turbidity current between different areas. The hydraulic and grainsize statistical parameters showed that low energy turbidity currents deposited the analyzed sediments. Almost all samples show a positive skewness due to the competency of the unidirectional flow of the transporting media, where the coarse end of the size frequency curve is "chopped off'. The kurtosis values in combination with the sorting values are plotted to the turbidity filed. A correlation between the mean palaeoflow velocity and the grain size showed that the mean palaeoflow velocities related to sandy silt samples whereas the higher velocities with sandy samples.